Os sentidos do trabalho voluntário : um estudo com membros de uma instituição luterana - Borchardt, Pietra (2015)
Work is a form of social relationship, constituting one of the main factors of human existence, which can generate satisfaction when it leads workers to meanings beyond the economic (ARAÚJO; SACHUK, 2007). Under the premises of the characteristics and the